Identification of Staphylococcus aureus Penicillin Binding Protein 4 (PBP4) Inhibitors - Mikaeel Young; Danica J. Walsh; Elysia Masters; Vijay Singh Gondil; Emily Laskey; Michael Klaczko; Hani Awad; James McGrath; Edward M. Schwarz; Christian Melander; Paul M. Dunman (MDPI AG, 2022)
Methicillin-resistant Staphylococcus aureus (MRSA) is a global healthcare concern. Such resistance has historically been attributed to the acquisition of mecA (or mecC), which encodes an alternative penicillin binding protein, PBP2a, with low β-lactam affinity. However, recent studies have indicated that penicillin binding protein 4 (PBP4) is also a critical determinant of S. aureus methicillin resistance, particularly among community-acquired MRSA strains. Thus, PBP4 has been considered an intriguing therapeutic target as corresponding inhibitors may restore MRSA β-lactam susceptibility. In addition to its role in antibiotic resistance, PBP4 has also recently been shown to be required for S. aureus cortical bone osteocyte lacuno-canalicular network (OLCN) invasion and colonization, providing the organism with a niche for re-occurring bone infection. From these perspectives, the development of PBP4 inhibitors may have tremendous impact as agents that both reverse methicillin resistance and inhibit the organism's ability to cause chronic osteomyelitis. Accordingly, using a whole-cell high-throughput screen of a 30,000-member small molecule chemical library and secondary assays we identified putative S. aureus PBP4 inhibitors. Quantitative reverse transcriptase mediated PCR and PBP4 binding assays revealed that hits could be further distinguished as compounds that reduce PBP4 expression versus compounds that are likely to affect the protein's function. We also showed that 6.25 µM (2.5 µg/mL) of the lead candidate, 9314848, reverses the organism's PBP4-dependent MRSA phenotype and inhibits its ability to traverse Microfluidic-Silicon Membrane-Canalicular Arrays (µSiM-CA) that model the OLCN orifice. Collectively, these molecules may represent promising potential as PBP4-inhibitors that can be further developed as adjuvants for the treatment of MRSA infections and/or osteomyelitis prophylactics.